The Relationship between Climate and Productivity of Tea Plants (Camellia sinensis L.) in Bah-Butong Gardens PT. Perkebunan Nusantara IV, North Sumatra Province in 2005-2009. - Siahaan, Aditya Johandry; Irsal; Sitorus, Bintang (Jurnal Online Pertanian Tropik, 2024)
Fluctuations in tea plant productivity are influenced by several climate factors, such as rainfall, number of rainy days, sunlight intensity, temperature and humidity. This research aims to evaluate the impact of climate factors on the productivity of Tea plants in the Bah-butong Plantation of PT. Perkebunan Nusantara IV, Simalungun Regency, North Sumatra. The hypothesis of this research is that rainfall, number of rainy days, sunlight intensity, temperature and humidity partially or simultaneously have a significant influence on the productivity of tea plants at the location. The research was conducted from September 2023 – Desember 2023, with data collection through field surveys and secondary data collection from related agencies. The data collected includes rainfall, number of rainy days, sunlight intensity, temperature, humidity and tea. The analysis method used is multiple linear regression and correlation analysis using statistical software SPSS.v.22 for Windows. The results of the regression analysis show that rainy days and temperature do not have a partially significant effect on increasing tea production. However, rainfall, amount of sunlight, humidity have a significant effect on increasing tea production. The results of the regression analysis show that rainfall, number of rainy days, sunlight intensity, temperature and humidity do not have a significant influence on increasing tea production.